2017
DOI: 10.7324/rjc.2017.1041936
|View full text |Cite
|
Sign up to set email alerts
|

"INVESTIGATION OF SOME CHEMICAL CONSTITUENTS, CYTOTOXICITY AND ANTIOXIDANT ACTIVITIES OF Beta Vulgaris var. altissima CULTIVATED IN EGYPT "

Abstract: The phenolic compounds were isolated for the first time from the alcoholic extract of the non-flowering aerial parts of Beta vulgaris var. altissima (sugar beet) and were identified as: Apigenin, Luteolin, Apigenin 7-O-di-glucoside, Luteolin 4'-O-rhamnoside, Caffeoyl-6-(3,4-dihydroxy benzoyl) β-D-glucoside, Apigenin 5-O-rhamnoside, Isoscutellarein 7-O-glucosyl-8-O-xyloside and 5, 7, 5'-trihydroxy-3'-methoxy flavone 4'-O-glucoside. The structures of the isolated compounds were elucidated through chromatographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…On other hand, the antioxidant FYGL extracted from Ganoderma lucidum reduces TG and total cholesterol content in liver cells by increasing the phosphorylation of AMP-activated protein kinase and acetyl-CoA carboxylase, which causes inhibition of FAS expression [17]. El-Hawary et al [7] it is reported that apigenin and luteolin in red beet have antioxidant activities. Therefore, the effects of red beet in lowing FAS gene expression can be related to the antioxidant properties of apigenin and luteolin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On other hand, the antioxidant FYGL extracted from Ganoderma lucidum reduces TG and total cholesterol content in liver cells by increasing the phosphorylation of AMP-activated protein kinase and acetyl-CoA carboxylase, which causes inhibition of FAS expression [17]. El-Hawary et al [7] it is reported that apigenin and luteolin in red beet have antioxidant activities. Therefore, the effects of red beet in lowing FAS gene expression can be related to the antioxidant properties of apigenin and luteolin.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, it has been shown that beet supplementation lowers blood pressure, weakens inflammation, prevents oxidative stress, maintains endothelial function, and restores cerebrovascular hemodynamics. El-Hawary et al [7] identified eight phenolic compounds, including apigenin and luteolin from B. vulgaris that have antioxidant activities. Apigenin reported decreased levels of plasma free fatty acid, total cholesterol, apolipoprotein B, and markers of liver dysfunction as well as increased hepatic steatosis and hepatomegaly, without altering dietary intake and adiposity in obese rats induced by a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%